Yoga for Adult Health - Susanti, Henny Dwi; Handayani, Tri Lestari; Aini, Nurul; Anggraini, Ika Rizky; Prasetyo, Yoyok Bekti; Ab Latif, Rusnani Binti (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2024)
ABSTRACT Yoga is an exercise that combines mind, spirit and body. This yoga combines breathing techniques, physical postures, relaxation and meditation. The aim of this community service is to improve the health of teenagers. This community service activity starts from the preparation stage, distributing questionnaires for pre-tests, explaining the purpose, benefits of yoga, steps for yoga exercises, and doing yoga exercises. Next, participants were given a questionnaire to assess the post-test. This activity was carried out in collaboration between the University of Muhammadiyah Malang and UiTM Cawangan Pulau Pinang Bertam Campus at the Az Zahra orphanage in Bandar Laguna Merbok, Sungai Tani, Kedah, Malaysia. Showed significant resultsthat teenagers understood the importance of yoga for health and they carried out the steps of yoga exercises. Yoga is very beneficial for the health of teenagers. It is best to do yoga every day to maintain both physical and psychological health in teenagers, so that health is maintained well. Keywords: Yoga, Adult, Physic, Psychology